2012
DOI: 10.1103/physrevlett.108.151601
|View full text |Cite
|
Sign up to set email alerts
|

Rapidity Renormalization Group

Abstract: We introduce a systematic approach for the resummation of perturbative series which involves large logarithms not only due to large invariant mass ratios but large rapidities as well. A series of this form can appear in a variety of gauge theory observables. The formalism is utilized to calculate the jet broadening event shape in a systematic fashion to next-to-leading logarithmic order. An operator definition of the factorized cross section as well as a closed form of the next-to-leading-log cross section are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
463
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(468 citation statements)
references
References 19 publications
5
463
0
Order By: Relevance
“…It will be shown that the RG evolution in the factorization scale µ f , whose anomalous dimension also depends on ζ 2 , has to be taken into account in order to derive an ultraviolet finite kernel. That is, the evolutions in both ζ 2 and µ f must be considered simultaneously for a consistent and complete treatment of the logarithmic corrections to the B meson wave functions, an observation in agreement with that in [39]. The solutions to the evolution equation contain the resummation of the rapidity logarithms, and their limits as ζ 2 → ∞ exist.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…It will be shown that the RG evolution in the factorization scale µ f , whose anomalous dimension also depends on ζ 2 , has to be taken into account in order to derive an ultraviolet finite kernel. That is, the evolutions in both ζ 2 and µ f must be considered simultaneously for a consistent and complete treatment of the logarithmic corrections to the B meson wave functions, an observation in agreement with that in [39]. The solutions to the evolution equation contain the resummation of the rapidity logarithms, and their limits as ζ 2 → ∞ exist.…”
Section: Introductionmentioning
confidence: 82%
“…The evaluation of the NLO effective diagrams for the B meson and pion wave functions indicates the existence of the double logarithm ln 2 ζ 2 P [36] and the single logarithm ln ζ 2 P [37], respectively 1 . These logarithms, with the same origin as the rapidity logarithms discussed in [34,38,39,40], need to be resummed as ln ζ 2 P becomes large. It is expected that the resummation of the rapidity logarithms in the B meson wave functions will reduce the scheme dependence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…different ways, and in this work we use the rapidity renormalization group [23,24]. This method regulates the rapidity divergences with an explicit factor in matrix elements, introducing a scale ν that functions much like µ in dimensional regularization.…”
Section: Jhep03(2014)119mentioning
confidence: 99%
“…For calculating the partonic FFs for producing a heavy quark pair in a non-relativistic S-wave state, the infrared (IR) divergence associated with contributions from individual Feynman diagrams completely cancels at any given order of α s after we sum up all contributions at this order. However, for calculating the partonic FFs of producing a heavy quark pair in a non-relativistic P -wave or higher orbital angular momentum state, IR divergences (as well as what is often referred to as the rapidity divergence [32][33][34][35][36] in the context of transverse momentum dependent factorization formalism [37]) cannot be completely canceled by summing over contributions from all diagrams [27]. Instead, IR divergences (and the rapidity divergences) should be cancelled by corresponding divergences in the NRQCD LDMEs on the RHS of the factorization formalism, as required by factorization.…”
Section: A Nrqcd Factorization and Input Fragmentation Functionsmentioning
confidence: 99%